Hidden cove - Tilly, Meg (Jove, 2019)
When Solace Island gallery owner Zelia Thompson's close friend Alexus Feinstein of the prestigious art gallery Feinstein & Co. dies of a "drug overdose," Zelia's intuition sounds an alarm. The Alexus she knew didn't do drugs and had everything to live for. As Zelia begins looking into the circumstances of her friend's death, what she uncovers will put her life in imminent danger. Will Zelia--with the help of the reclusive crime fiction novelist Gabe Conaghan--be able to unravel the mysterious happenings surrounding Alexus's untimely death? Or will she become the bloodthirsty artist's next victim?